2000
DOI: 10.2460/ajvr.2000.61.1106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral administration of metronidazole on small intestinal bacteria and nutrients of cats

Abstract: Oral administration of metronidazole decreased the number of aerobic bacteria and altered indigenous flora in the small bowel of cats. Normal duodenal flora appeared to be stable, because species of bacteria were re-established by 9 months after cessation of metronidazole. Bacterial flora appeared to have an impact on nutrients, because albumin and cobalamin increased during antibiotic administration and returned to preadministration concentrations after cessation of the antimicrobial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…However, recent studies have shown that the total Volume 26, Number 2, May 2011 number of bacteria is very variable and can exceed those numbers from time to time even in healthy dogs or cats. [66][67][68] Therefore, to make a diagnosis of bacterial overgrowth, bacterial counts of duodenal juice should be above 2.7 ϫ 10 9 cfu/mL or 1.1 ϫ 10 9 cfu/mL in dogs and cats, respectively. 66 Moreover, aside from quantification of the total number of bacteria, imbalances between the different species of the intestinal bacterial populations are probably also important.…”
Section: Tests Of Bacterial Overgrowthmentioning
confidence: 99%
“…However, recent studies have shown that the total Volume 26, Number 2, May 2011 number of bacteria is very variable and can exceed those numbers from time to time even in healthy dogs or cats. [66][67][68] Therefore, to make a diagnosis of bacterial overgrowth, bacterial counts of duodenal juice should be above 2.7 ϫ 10 9 cfu/mL or 1.1 ϫ 10 9 cfu/mL in dogs and cats, respectively. 66 Moreover, aside from quantification of the total number of bacteria, imbalances between the different species of the intestinal bacterial populations are probably also important.…”
Section: Tests Of Bacterial Overgrowthmentioning
confidence: 99%
“…The present study set out to determine if compression coating immediate‐release RDZ tablets with guar gum could modify the RDZ release to target the colon in healthy cats using pharmacokinetic methods after a single dose. Because metronidazole, another nitroimidazole drug, significantly decreases aerobic and anaerobic bacterial counts in the duodenum of healthy cats, we were concerned that repeated RDZ dosing could sufficiently alter colonic flora with repeated administration, which would alter guar gum digestion and prevent RDZ release (Johnston et al ., ). Previous in vitro studies with rat caecal contents have shown that administration of either metronidazole or tinidazole interferes with degradation of guar gum matrix tablets by colonic bacteria (Krishnaiah et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…It is reasonable to attribute some of these differences, as those between FISH-and PCR-based methods, to differences in technology, with the most likely explanation being that the Table 1. The microbiota present in the feline small intestine based on culture Osbaldiston and Stowe (1971) Papasouliotis et al Data are cited from Osbaldiston and Stowe (1971), Papasouliotis et al (1998), and Johnston et al (2000). N/A: data were not available, ND: organism was not detected.…”
Section: Studies Involving Molecular Methodsmentioning
confidence: 99%
“…Several studies have evaluated the bacterial composition of the proximal part of the small intestine, the colon and feces (Osbaldiston and Stowe, 1971;Terada et al, 1993;Sparkes et al, 1998a, b;Johnston et al, 2000Johnston et al, , 2001. Tables 1 and 2 summarize the results of those studies.…”
Section: Composition Of the Gi Microbiotamentioning
confidence: 99%